2011
DOI: 10.1590/s0102-311x2011001500014
|View full text |Cite
|
Sign up to set email alerts
|

Birth cohort differences in the use of medications in a Brazilian population of older elderly: the Bambuí cohort study of aging (1997 and 2008)

Abstract: This study examined differences in the use of medications in two birth cohorts (born from 1916 to 1926 and from 1927 to 1937) wave, in 2008 (n = 620). The number of medications currently consumed (mean = 4.6 and 3.4, respectively) and prevalence of polypharmacy (46.6% and 29.1%, respectively) The high prevalence of chronic illnesses among the elderly is associated with high consumption of medications by this population group 3 . In the elderly population, the risks associated with consumption of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(62 reference statements)
2
6
0
4
Order By: Relevance
“…Likewise, cardiac therapy (ATC-group C01) showed considerable consumption; this result is similar to that of Straand and Rokstad (1999), where nitrates and digitalis preparations were more representative drugs. Other studies showed the same tendencies (Loyola et al, 2011;Rozenfeld, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, cardiac therapy (ATC-group C01) showed considerable consumption; this result is similar to that of Straand and Rokstad (1999), where nitrates and digitalis preparations were more representative drugs. Other studies showed the same tendencies (Loyola et al, 2011;Rozenfeld, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…In this way, new demands arise in terms of public health policies 8 . Chronic conditions have greater visibility in the health care with the aging of the population 15 . In this way, the increased burden of disease and the use of medications become challenges for the system 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Around 80.0% of Brazilians aged more than 60 years take at least one medication per day, which highlights the need to evaluate the determinants of this use, and especially adherence to treatment. 4,6,12 Adherence to treatment is the degree to which the individual's behavior and the doctor or health care professional's guidance are in agreement. 16,27 Low adherence may negatively affect the patient's clinical evolution, leading to personal, social and economic consequences.…”
mentioning
confidence: 99%